Implementation of Regional Regulation Number 13 of 2002 Concerning the Prohibition of the Alcoholic Beverages Circulation in Malinau Regency - Mario Yosef Riberu; Muhlis Hafel; Darmanto darmanto (International Journal Labs, 2024)
Regional Regulation Number 13 of 2002 concerning the Prohibition of the Circulation of Alcoholic Beverages in Malinau Regency is a guideline in the implementation of programs and policies to maintain and protect every citizen, especially the residents of Malinau Regency in order to avoid the use of alcoholic beverages and abuse in the social life of the community. The purpose of the research is to find out the Implementation of Regional Regulation Number 13 of 2002 concerning the Prohibition of the Circulation of Alcoholic Beverages in Malinau Regency, and to find out the obstacles and find solutions to overcome the obstacles faced by the Malinau Regency Regional Government in enforcing the regional regulations. This study uses qualitative descriptive research, to find out the population in this study is to use a sample to find out the extent of the implementation of the local regulation on the prohibition of alcoholic beverages in the community whether it has been fully implemented. This research instrument uses library study methods and field research which includes observation, interviews and documentation techniques. Method for Data Analysis in this study uses qualitative data analysis of an interactive model consisting of data collection, data reduction, data presentation, and conclusion drawn. The results of the study illustrate that the problems faced in the implementation of Regional Regulation Number 13 of 2002 concerning the Prohibition of the Circulation of Alcoholic Beverages in Malinau Regency such as the lack of socialization carried out by the Regional Government to the community, the absence of financial support for agencies or implementing agencies in the context of socialization and implementers that are very lacking compared to the area of the area which is not in accordance with the number of implementers or implementers that exist. In addition, it is necessary to improve bureaucratic reform so that the purpose and implementation of the prohibition regulation can be more optimal.